Condicionantes políticos das reformas tributárias na América Latina - Almeida, Aloisio Flávio Ferreira de (2015)
Are tax reforms conditioned by political factors? Checking the scarcity of empirical studies on the subject, we define tax reform and adopt a typology for these phenomena. We then compiled the tax reforms database, obtained from the responses to forms of the IPES 2006, a survey held by the Inter-American Development Bank with support from the Inter-American Center of Tax Administrations (CIAT). These forms were completed by expert officials from the ministries of finances of Latin American countries, who reported tax reforms between 1990 and 2004. We then built the indexes of tax reforms, which were used as dependent variables in our regression models. The indices contribute to the development of quantitative studies on tax reforms in Latin America. They allow us to separately analyze the determinants of reform of the taxation of income and consumption, as well as general and targeted reforms, and those reforms aimed at the increase or decrease of public revenues. The tests highlighted the influence of the closed list in proportional representation electoral systems, indicating that the parliamentary discipline is important to adopt reforms. For some specifications, district magnitude, bicameralism, the power of decree of the president of the republic and its electoral cycle, all showed some relevance to tax reforms. We do not collect evidence of short-term political factors, such as the government party ideology and government majority in parliament. Similarly, the influence of presidential powers of agenda and veto was not confirmed. The domain of a party in the coalition government was relevant only when linked to the closed list. Overall, the results confirm the impact of political-institutional factors on tax reforms. The same cannot be said for political-situational factors. In addition, differences were observed in the political constraints that define reforms in taxation of income and consumption, targeted and general reforms, expansive reforms and fiscal incentives. The study contributes to quantitative analysis of the political constraints of tax reforms in Latin America and provides data previously unavailable. It shows empirical evidence, considering different types of reform and political factors. It concludes by the need to incorporate the political variables in studies involving tax reforms, previously marked by the dominance of economic arguments. It also suggests that better political institutions are important to improve tax policy decisions in Latin America.